Stylized robotic clay sculpting. (August 2021) - Ma, Zhao; Duenser, Simon; Schumacher, Christian; Rust, Romana; Baecher, Moritz; Gramazio, Fabio; Kohler, Matthias; Coros, Stelian
Highlights: An interactive design system to design sculpting styles and robotically fabricate on clay material. A divide-and-conquer strategy for independent assigning of sculpting styles over complex geometries. Multi-objective optimization for path planning of toolpath-driven robotic fabrication. Sculpting style exploration and analysis inspired by painting brushstroke for robotic clay sculpting. Graphical abstract: Abstract: This paper presents an interactive design system that allows the user to create and fabricate stylized sculptures in water-based clay, using a standard 6-axis robot arm. This system facilitates the materialization of abstract design intentions into clay, through the algorithmic formulation of sculpting styles, the optimal path planning of the sculpting toolpaths, and a subtractive robotic fabrication process using customized tools. Unlike other precision-driven fabrication technologies, the authors embrace artistic uncertainty by conducting manual and robotic sculpting experiments and incorporating prominent parameters that affect the fabrication quality. The versatility of the described approach is demonstrated by designing a series of sculpting styles over a wide range of 3D models and robotically fabricating them in clay. Additionally, the paper explores various strategies for designing stylized robotic sculpting patterns by generating toolpaths informed by different techniques.